Statistical Study on the North‐South Asymmetric Distribution of the Mid‐Low‐Latitude Nightside Disturbed Magnetic Fields. Issue 3 (16th March 2022) - Ou, Jiaming; Du, Aimin; Ge, Yasong; Luo, Hao; Zhang, Ying; Guo, Zhifang
Abstract: The nightside magnetic field at the middle and low latitude observatory is usually disturbed, decreasing in its north component (noted as Bx ) during the periods of enhanced space weather activity. As indicated by the SYM‐H index, the decreasing field mainly originated from the magnetospheric westward ring current and the cross‐tail currents. In the meridian direction, the maximum of the disturbed field has been observed not always located at the geomagnetic dipole equator. One possible explanation is that the latitudinal position of the magnetotail current systems is affected by the orientation of solar wind to the Earth's geomagnetic dipole axis (noted as tilt angle). For a non‐zero tilt angle, the current deviates from the equatorial position (e.g., Malin & Mete Işikara,  1976; 10.1111/j.1365-246x.1976.tb07096.x ). In this study, the mid‐low latitudinal distribution of the nightside disturbed field is systematically investigated every ∼1.5 hr, based on the magnetic surveys of the Swarm satellite constellation at polar orbits of ∼450 km altitude. The meridian distribution of Bx regularly appears like an upward‐opening parabolic shape with its vertex representing the magnetic minimum. In summer, the minimum is found generally located in the southern hemisphere, while in winter the pattern is reversed. The overall distribution demonstrates north‐south asymmetry. When the disturbed level is low, the deviation of the magnetic minimum from the dipole equator usually gets larger. The north‐south asymmetric distribution during storm times is further analyzed. In the initial phase, the magnetic minimum was shifted prominently (about 10°–30°) from the equator, then moved back (with the offset less than 10°) in the main phase and recovery phase in most cases. Moreover, the latitudinal deviation undergoes a diurnal variation, which is conspicuous in spring and autumn. It seems the asymmetric distribution is anti‐correlated to the contribution of the ring current, indicated by the SYM‐H index. The warping structure of the cross‐tail current sheet probably plays a predominant role in generating the north‐south asymmetry of the magnetic field disturbances for non‐zero dipole tilt angles. Monitoring the external magnetic configuration via the low‐Earth‐orbit satellites will provide fundamental evidence to identify the relative position of the ring current and the cross‐tail current, as well as the dynamic processes in the near magnetotail. Key Points: The nightside magnetic disturbed maximum at mid‐low latitudes annually shifts in meridian direction, which is notable when SYM‐H is quiet The disturbed maximum generally stayed close to the dipole equator in the main phase and the recovery phase of the geomagnetic storm The cross‐tail current largely contributes to the near‐Earth disturbed fields, dominating the magnetic north‐south asymmetric distribution